Identifikasi Molekuler Cowpea mild mottle virus pada Tanaman Kedelai di Jawa - Umi Kulsum; Sedyo Hartono; Sri Sulandari; Susamto Sumowiyarjo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Soybean (Glycine max) is an important food crops in Indonesia, but the production is considered low. Infection of Cowpea mild mottle virus (CPMMV) may affect to the productivity of the crops. The virus cause a variety of symptoms on soybean such as mosaic, chlorosis, necrosis, distortion, and leaf dwarf. The aims of this study were to detect and identify CPMMV by molecular technique from some varieties of soybeans, i.e. ‘Anjasmoro’, ‘Argomulyo’, ‘Grobogan’, and two local Edamame varieties. Symptomatic samples was obtained randomly from main soybean growing areas in Java. DNA amplification using specific primer for coat protein of CPMMV was only successfully gained from leaf samples of var. Argomulyo from Malang which showing mosaic on the leaf surface, vein clearing, and chlorosis. Further amino acid and nucleotide sequence analysis showed that this CPMMV isolate has highest homology (99%) to CPMMV isolate of French bean from China.